Optical thermometry based on up-conversion luminescence of Tm3+ doped transparent Sr2YF7 glass ceramics - Chen, WeiPing; Hu, FangFang; Wei, RongFei; Zeng, QingGuang; Chen, LiPing; Guo, Hai (Journal of luminescence, 2017)
Tm3+/Yb3+ co-doped transparent glass ceramics (GC) containing Sr2YF7 nanocrystals were successfully manufactured by traditional melt-quenching technique. Their structural and up-conversion luminescent properties were systemically investigated through X-ray diffraction (XRD), transmission electron microscope (TEM) and a series of spectroscopy methods. Tremendously enhanced up-conversion emissions with obvious Stark splitting and prolonged luminescence lifetime were observed after crystallization. These optical spectroscopy results manifest that Tm3+ ions have incorporated into the Sr2YF7 crystalline lattice with low phonon energy (~ 400cm−1) after heat-treatment. The 3F2,3 and 3H4 levels of Tm3+ can be explored as thermally coupled energy levels (TCEL) for temperature sensing because of their befitting energy gap (~ 2000cm−1). At the same time, the population of 1G4 state of Tm3+ is indirectly originated from 3H4 one. Therefore the temperature sensing performances of Tm3+ doped Sr2YF7 GC were investigated by fluorescence intensity ratio (FIR) between 3F2,3 → 3H6 and 1G4 → 3F4 up-conversion emissions of Tm3+. Results show that the theoretical maximum value of relative sensitivity SR-max is 1.16%K−1 at 428 K, and absolute sensitivity SA keeps increasing with temperature. Such Tm3+/Yb3+ co-doped Sr2YF7 GC may be excellent candidate for optical temperature sensors.